2018
DOI: 10.1080/10903127.2018.1511017
|View full text |Cite
|
Sign up to set email alerts
|

Automated External Defibrillator Geolocalization with a Mobile Application, Verbal Assistance or No Assistance: A Pilot Randomized Simulation (AED G-MAP)

Abstract: In a simulated environment, verbally providing OHCA bystanders with the nearest PAED's location appeared to be effective in reducing the time to defibrillation in comparison to no assistance and to an AED geolocalizing mobile app, but further research is required to confirm this hypothesis, ascertain the external validity of these results, and evaluate the real-life implications of these strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…A recent simulation study found that verbal direction to the nearest public access AED was more effective than either no directional assistance or assistance via an AED geolocation mobile application. 11 Current barriers to this strategy include lack of systematically registered and maintained AEDs and integration with 9-1-1 dispatch systems. As highlighted by the findings in this study, strategies to direct bystanders to the closest AED will also need to take into consideration potential access barriers, such as roads, stairs, locked doors, and AED signage, which is not currently regulated or systematic.…”
Section: Discussionmentioning
confidence: 99%
“…A recent simulation study found that verbal direction to the nearest public access AED was more effective than either no directional assistance or assistance via an AED geolocation mobile application. 11 Current barriers to this strategy include lack of systematically registered and maintained AEDs and integration with 9-1-1 dispatch systems. As highlighted by the findings in this study, strategies to direct bystanders to the closest AED will also need to take into consideration potential access barriers, such as roads, stairs, locked doors, and AED signage, which is not currently regulated or systematic.…”
Section: Discussionmentioning
confidence: 99%
“…In a simulation study from Quebec, Canada, researchers found that a passive AED mapping app improved time to AED retrieval compared with having no guidance at all but was not as effective as verbal instructions from an emergency call taker. 173 In another simulation study from Japan, a passive AED mapping app did not improve time to AED retrieval. 174…”
Section: Innovative Approaches To Public-access Defibrillationmentioning
confidence: 97%
“…In a simulation study from Quebec, Canada, researchers found that a passive AED mapping app improved time to AED retrieval compared with having no guidance at all but was not as effective as verbal instructions from an emergency call taker. 173 In another simulation study from Japan, a passive AED mapping app did not improve time to AED retrieval. 174 Other, more sophisticated systems are able to link networks of community volunteers with local emergency dispatch centers to facilitate AED retrieval, bystander CPR, and AED use.…”
Section: Clinical Statements and Guidelinesmentioning
confidence: 97%
“…Mobile devices have the potential to increase this by assisting with the retrieval and use of AEDs. Multiple apps have been created to locate AEDs in the vicinity of the user, although with mixed results in simulations 190‐192 . Barriers include the accuracy of AED location databases, size of the user base, app interface, and the availability of multiple apps instead of a single validated regional, national, or international standard.…”
Section: Mhealth Applications For Arrhythmiasmentioning
confidence: 99%